Conditional Symmetry and Exact Solutions of a Multidimensional Diffusion Equation - Barannyk, T. A. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We investigate the conditional symmetry of a multidimensional nonlinear reaction–diffusion equation by its reduction to a radial equation. We construct exact solutions of this equation and infinite families of exact solutions for the corresponding one-dimensional diffusion equation.